State regulation of the restaurant business in ukraine: implementation of the HACCP System (Hazard Analysis and Critical Control Points) (Economics and region, 2025)
The article examines topical issues related to the implementation of the Hazard Analysis and Critical Control Points (HACCP) system in Ukraine as an important direction of state regulation in the restaurant business sector. It is established that the HACCP system has been formed as a universal international instrument for ensuring proper quality control of food products in restaurant enterprises. The experience of foreign countries demonstrates that the effectiveness of HACCP functioning is ensured not only by its technical component, but also by state support in regulatory and institutional aspects. In 1997, the National Advisory Committee on Microbiological Criteria for Foods (NACMCF) adopted the HACCP principles and application guidelines developed for use in all sectors of the food industry, namely from cultivation and harvesting to processing, production, distribution, merchandising, and food preparation for consumption. The analysis of the regulatory and legal framework in the studied area indicates the adaptation of HACCP standards in Ukraine, which requires the integration of international experience with national regulations and current legislation. In Ukraine, a system of state control and supervision over the implementation of permanent procedures based on HACCP principles has been established, which falls within the competence of the State Service of Ukraine on Food Safety and Consumer Protection. It is determined that the implementation of HACCP principles in restaurant establishments has a number of advantages and disadvantages that depend on the organizational, economic, and financial capacities of restaurant businesses, which necessitates strengthened state support, in particular through economic incentives, professional training of personnel for the restaurant industry, and other supportive measures.
Keywords: state regulation; restaurant business; public catering establishments; institutional aspect; regulatory and legal aspect; sanitary and hygienic standards; food safety; HACCP system; quality management